2019
DOI: 10.1139/apnm-2018-0643
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of acute aerobic exercise but not aerobic fitness impacts on corticospinal excitability

Abstract: Aerobic exercise (AE) modulates cortical excitability. It can alter both corticospinal excitability and intra-cortical networks, which has implications for its use as a tool to facilitate processes such as motor learning, where increased levels of excitability are conducive to the induction of neural plasticity. Little is known about how different intensities of AE modulate cortical excitability or how individual-level characteristics impact on it. Therefore, we investigated whether AE intensities, lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Although we intended to acquire data from 22 participants, only 19 were available to us. However, a recent study from MacDonald et al [9] observed an increase in MEPs after moderate intensity cycling in a sample of 15 participants who ranged from sedentary to fit. Therefore, it is unlikely that the lack of effect we observed is due to a limited sample size.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Although we intended to acquire data from 22 participants, only 19 were available to us. However, a recent study from MacDonald et al [9] observed an increase in MEPs after moderate intensity cycling in a sample of 15 participants who ranged from sedentary to fit. Therefore, it is unlikely that the lack of effect we observed is due to a limited sample size.…”
Section: Discussionmentioning
confidence: 92%
“…This is in line with previous work showing no change in corticospinal excitability following moderate- [3][4][5][6] and high-intensity exercise [10] in low fit individuals. Increases in corticospinal excitability following exercise have only been observed in high fit individuals after moderate intensity exercise [6,8,9], although some studies have reported to change after moderate intensity exercise [7,11]. Opie and Semmler (2019) also recently showed increased MEP amplitude after both high-intensity interval training and low-intensity continuous exercise, although fitness of the participant sample tested was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations